Synthesis of Uniform, Monodisperse, Sophorolipid Twisted Ribbons. Issue 11 (28th August 2015) - Cuvier, Anne‐Sophie; Babonneau, Florence; Berton, Jan; Stevens, Christian V.; Fadda, Giulia C.; Genois, Isabelle; Le Griel, Patrick; Péhau‐Arnaudet, Gérard; Baccile, Niki
Abstract Control over size monodispersity in chiral self‐assembled systems is important for potential applications like templating, tissue engineering or enantioselective chromatography, just to cite a few examples. In this context, it was reported that the saturated form of sophorolipids (SL), a bioderived glycolipid, are able to form self‐assembled twisted ribbons in water at neutral pH. Here, we show the possibility to control their size dispersion, generally between 10 and 40 nm after synthesis to a value of 13.5±1.5 nm, by a simple dialysis step eliminating the excess of NaCl. We use transmission electron microscopy under cryogenic conditions (cryo‐TEM) combined with small angle neutron scattering (SANS) to characterize the ribbon dispersion both visually and statistically. Two negative controls show the importance of salt in the aggregation process of the ribbons.